Percepción de un grupo de personas sobre su participación en estudios clínicos con medicamentos en la ciudad de Cali - González Castaño, Mauricio (Universidad Antonio Nariño, 2022)
Perception is a process that develops in a personal and subjective way in each human being, which was built based on previous life experiences, socioeconomic and sociocultural conditions in which he/she was immersed, allowing us to learn and understand the universe of beliefs, values and imaginaries that lie in the mind of everyone. Therefore, the objective of this research is to analyze the perception of a group of people about their participation in clinical studies with drugs in the city of Cali. Thus, it describes the perspective they have on this aspect, identifying the risks to which they feel exposed and characterizing the benefits they consider they can obtain after their participation in this type of studies